Winding AC loss reduction techniques in the slot of high – frequency electrical machines - Bardalai, Anuvav (2019)
In recent years, the demand for high performance electrical machines that combine high power density (kW/kg or kW/L), light – weighting and high efficiency have become more and more important. High power density reduces the volume, weight of the machines and offers great potentials to reduce cost. Increasing the rotational speed of the machines provides a straightforward solution to reduce the size of the machine. However, increasing the rotational speed increases the fundamental frequency of the machine. These elevated frequencies lead to parasitic effects such as skin and proximity effect, causing the losses in the winding to increase significantly. For traction applications, often low voltage high power density machines combined with low-cost manufacturing are desired. As such, solid straight round magnet wires are employed which offer great potential in ease of manufacturing and overall cost reduction. However, these wires are subjected to high AC losses in the high frequency operations where the machine often needs to operate. Therefore, mitigation of these AC losses in these machines have become the subject of prime importance in the recent years. In this work, the main aim is to investigate these AC losses in the windings of a high – frequency interior permanent magnet machine and propose possible methods to mitigate the losses generated in the windings. An in-depth investigation into the effects of these losses in the winding is presented and it is shown that while the skin and proximity effects losses in the strands do not depend on the shape and position of the bundles, the circulating currents are very sensitive to the bundle shape. Using Finite Element Method, it is shown how for a given slot geometry, by selecting optimum strand diameter and winding height, the effects of AC losses in the winding can be mitigated. A reduction of 34% of the total losses in the winding is achieved by selection of optimum strand size and winding height in the machine investigated in this thesis. Taking advantage of the advancements in 3D printing technology, slot formers with holes along the length are manufactured to achieve accurate placement of each strand to match the corresponding positions as in the FE model. With these motorettes, it is shown that FE models can be validated by experimental results. In this work, the accuracy is within 10% of the experimental test results. Using FEM, it is shown that by carefully controlling the shape of the conductors near the slot top (area of the machine slot towards the slot opening), the AC losses in the winding can be significantly reduced. In this work, a reduction of 36% in the AC losses at the active length (stack length of the machine) is achieved. It is also shown that the effect of individual strand positions within a bundle shape is not critical if the bundle shapes are fixed. Using experimental motorette setups with randomly wound winding, a relationship between copper filling factor and AC losses is presented where the trend shows that for the same strand diameter size, with increase in slot filling factor the ratio of total loss in the winding to equivalent loss if only DC was flowing (Total/DC) increases. Comparing the motorettes with the same winding specification as of the prototype machine, this analysis shows that for random wound winding the losses in the winding can be unpredictable and with smaller strands diameters/ more strands – in – hand, the losses in the windings can be significantly high.